2018
DOI: 10.1038/s41467-018-06447-z
|View full text |Cite
|
Sign up to set email alerts
|

Correcting glucose-6-phosphate dehydrogenase deficiency with a small-molecule activator

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency, one of the most common human genetic enzymopathies, is caused by over 160 different point mutations and contributes to the severity of many acute and chronic diseases associated with oxidative stress, including hemolytic anemia and bilirubin-induced neurological damage particularly in newborns. As no medications are available to treat G6PD deficiency, here we seek to identify a small molecule that corrects it. Crystallographic study and mutagenesis analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 62 publications
1
116
4
Order By: Relevance
“…[16,17] Encouraged by the discovery of Alda-1, we set out to identify small molecules that enhance the activity of pathogenicm utants of G6PD. [19] First, we found that analogues (e.g., 3,S cheme 1) prepared using the pharmacophore of the structure provided by the vendor( 1)w ere inactive. [18] As mall-molecule activatoro fs everalp athogenic forms of G6PD (AG1 (2), Scheme 1) was identified from the screen, and ad etailed mechanistic understanding of AG1 was required to further our translational objectives.…”
mentioning
confidence: 99%
“…[16,17] Encouraged by the discovery of Alda-1, we set out to identify small molecules that enhance the activity of pathogenicm utants of G6PD. [19] First, we found that analogues (e.g., 3,S cheme 1) prepared using the pharmacophore of the structure provided by the vendor( 1)w ere inactive. [18] As mall-molecule activatoro fs everalp athogenic forms of G6PD (AG1 (2), Scheme 1) was identified from the screen, and ad etailed mechanistic understanding of AG1 was required to further our translational objectives.…”
mentioning
confidence: 99%
“…Furthermore, implementing G6PD deficiency screening tests at PHC clinics will help improve Ghana's malaria control program as well as contribute to Ghana's quest to attain universal health coverage. Moreover, the ability of health providers in resource-limited settings to test the G6PD deficiency status of pregnant women potentially can help them report promptly hemolytic anemia cases caused by G6PD deficiency may during pregnancy management to prevent hematological and several possible serious obstetrical complications such as fetus malformations, infertility, bilirubin-induced neurological damage in newborns, and death [6,40]. In view of these, we recommend a wider implementation of appropriate diagnostic tests for G6PD deficiency testing in rural and resource-limited settings health facilities to improve G6PD deficiency status testing of pregnant women and patients prior to the administration of SP and other antimalaria medicines as well as, facilitate the malaria control/elimination programs with primaquine in malaria-endemic countries.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the health facility-to-population ratio for G6PD deficiency POC testing in UER was approximately 1:159,210 (8/1,273,677) population, whilst the health facility-to-women of reproductive age (WORA) was about 1:38,210 (8/305683). Of these eight hospitals, six (6) were District Hospitals owned and managed by the GHS, one (1) owned by a Church (a member of the CHAG), and one (1) Regional Hospital. Of the thirteen administrative districts in the region, five districts (Binduri, Nabdam, Garu-Tempane, Pusiga, and Builsa South) had no health facility providing G6PD deficiency POC testing, as shown in Figure 1.…”
Section: Geographical Distribution Of Public Health Facilities Providmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of G6PD extended lifespan of transgenic HD fly significantly 99 Drosophila transgenic model Overexpression of G6PD in Drosophila neurons delayed proteostasis decline with age and extend lifespan 21 Transgenic mice with moderate expression of G6PD Moderate transgenic overexpression of G6PD in mice extended healthspan and median lifespan of females 24 Development of a G6PD agonist G6PD agonist AG1 effectively activated G6PD and reduced oxidative stress in G6PD-deficient human fibroblasts and zebrafish embryo 22 Abbreviations: G6PD, glucose-6-phosphate dehydrogenase; OGD, oxygen-glucose deprivation; PPP, pentose phosphate pathway. TANG | 14291…”
Section: Models Key Findings Referencesmentioning
confidence: 99%